CHARACTERISTIC OF TECHNICAL OPERATION OF POLE AND LINE OPERATION IN KM SARI USAHA 09 WITH THE MINISTERIAL REGULATION 36 OF 2023 - Hutapea, Roma Yuli; Ramadhan, Rizki; Tiku, Mathius; Mardiah, Ratu Sari; Widagdo, Aris (Politeknik Kelautan dan Perikanan Dumai, 2024)
Pole and line is a fishing gear consisting of a fishing rod or bamboo which has a main rope, secondary rope and hook and is operated by hand with the target of skipjack tuna. Sometimes there are still fishermen who do not carry out fishing activities based on applicable regulations. The study was carried out in Bitung with the aim of knowing pole and line fishing techniques, identifying the technical linkages of pole and line fishing in KM. Sari Usaha 09 with Permen KP 36 of 2023 and uses observation, documentation, and interview methods then is analyzed by descriptive and comparative. The technical connection between pole and line operations has discrepancies in Permen KP 36 of 2023 with result research data with the criteria for vessel size, fishing line, FADs. Criteria for hook and rod length were taken from 3 journals/references on the operation of pole and line fishing gear in the North Sulawesi region. There is a discrepancy in the criteria for pole and line fishing gear because Permen KP 36 of 2023 does not discuss fishing hooks and rod length, so journals/references regarding the operation of pole and line fishing gear in the North Sulawesi region are cited. Regarding the results of the KPA regarding technical comparisons of pole and line operations with Permen KP 36, it is known that four criteria are suitable and one is not suitable, namely boat size, fishing line, FADs, and rod length while the criteria are not suitable, namely, hook size.